Drought in intermittent river and ephemeral stream networks. Issue 5 (22nd December 2021) - Sarremejane, Romain; Messager, Mathis Loïc; Datry, Thibault
Abstract: Intermittent rivers and ephemeral streams (IRES), those watercourses that periodically cease to flow or dry, are the world's most widespread type of river ecosystem. Our understanding of the natural hydrology and ecology of IRES has greatly improved, but their responses to extreme events such as drought remain a research frontier. In this review, we present the state of the art, knowledge gaps and research directions on droughts in IRES from an ecohydrological perspective. We clarify the definition of droughts in IRES, giving recommendations to promote transferability in how ecohydrological studies characterize droughts in non‐perennial stream networks. Based on a systematic search of the literature, we also identify common patterns and sources of variation in the ecological responses of IRES to droughts and provide a roadmap for further research to enable improved understanding and management of IRES during those extreme hydrological events. Confusion in the terminology and the lack of tools to assess the hydrological responses of IRES to drought may have hindered the development of drought research in IRES. We found that 44% of studies confused the term drought with seasonal drying and that those that measure droughts in a transferable way are a minority. Studies on ecological responses to drought in IRES networks are still rare and limited to a few climatic zones and organisms and mainly explored in perennial sections. Our review highlights the need for additional research on this topic to inform IRES management and conservation.